Potential of Tamarind (Tamarindus indica L.) leaves as funtional food - Dewi, Kifayati Rosiyanti; Wahyudi, Ari; Pangestuti, Meitriana (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Public interest in functional foods, which provide health benefits beyond basic nutrition, is growing in Indonesia and worldwide. Despite their recognized medicinal properties, tamarind leaves remain underutilized in functional food applications. This review examines their potential as a valuable local resource for disease prevention. Methods: A literature search on